The Need to Use Private Investment to Financing Educational Institutions - Sharapova Mashkhura Azadovna (Peerian Journals Publishing, 2023)
This article highlights the need to use private investment along with public funds in financing the education system, in particular, secondary schools, and also analyzes projects that are planned to be implemented in cooperation with international financial organizations.
Keywords: education financing; secondary schools; international financial organizations